Pedestrian smartphone overuse and inattentional blindness: an observational study in Taipei, Taiwan - Ping-Ling Chen; Chih-Wei Pai (BMC, 2018)
Abstract Background Smartphone addiction has become a crucial social issue. Past studies have indicated that phone use such as talking or texting while walking constitutes a dual task that may cause pedestrians inattentional blindness and impair their awareness of surroundings. Methods This study investigated the influence of various smartphone tasks (calling, music listening, texting, playing games, and web surfing) on the smartphone overuse and inattentional blindness of pedestrians in Taipei, Taiwan. Pedestrian smartphone overuse was observed and recorded via WiFi cameras to determine whether pedestrians were using their smartphones when crossing a street with a signal. After crossing the street, pedestrians were interviewed to obtain additional information regarding demographics, smartphone tasks, data plan, and screen size. Pedestrians were classified into the case (distracted) and control (undistracted) groups. By determining whether pedestrians saw something unusual-a clown walking the opposite direction-and heard the national anthem played by the clown, inattentional blindness and deafness were examined. Pedestrians' situational awareness was assessed by ascertaining whether they remembered how many seconds remained before the crossing signal upon arriving at the curb. Results In total, 2556 pedestrians crossed the street and underwent the interview. Smartphone overuse and inattentional deafness were the commonest among music listeners. Playing Pokémon Go gaming was the task most associated with inattentional blindness. Logistic regression models revealed that contributing factors to smartphone overuse and inattentional blindness were a large smartphone screen (≥5 in), unlimited mobile Internet data, and being a student. The interactions of gaming with being a student and with unlimited data were significantly associated with smartphone overuse, inattentional blindness and deafness, and situational awareness. Conclusions Listening to music was the smartphone task most associated with pedestrian smartphone overuse and inattentional deafness. Pokémon Go was the most associated task with inattentional blindness and reduced situational awareness.